Microinterations, macro results: why you should design the details - Betz, Sonya; Hall, Robyn (My University, 2014)
Details matter. Each of these presentations share tips and advice on getting the interactions and content on your website right for your users. MacEwan librarians look at how micro-interactions, the moments when we delight our users by refining the way we offer services, lead to macro-results. Get concrete recommendations for designing positive micro-interactions with library users in mind. Speakers use their own experience designing a new institutional repository to outline steps to identify, refine, and test micro-interactions with users, and highlight the impact of their strategy on the overall user experience.
Presented on October 27, 2014 at the Internet Librarian Conference in Monterey, California.
Keywords: user testing; web design; institutional repositories; microinteractions; usability